2011
DOI: 10.5897/sre10.496
|View full text |Cite
|
Sign up to set email alerts
|

Study of cutting force and surface roughness in milling of Al/Sic metal matrix composites

Abstract: In this experimental study, composite samples containing silicon are produced with powder metallurgy technique by sintering under argon atmosphere. The effect of cutting speeds, feed rates and different cutting tool types on cutting forces and surface roughness are investigated in the face milling operation of silicon carbide particle reinforced aluminium metal matrix composites. Machining operations are conducted using coated and uncoated tools. Main cutting force (F x ) and surface roughness (Ra) are measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 22 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…In milling processes, by using Taguchi method and ANOVA analysis, the cutting forces and surface roughness could be investigated based on a number of factors, such as depth of cut, feed rate, cutting speed, cutting time, workpiece hardness, etc. Several research works had been conducted in different conditions and had also been applied for different workpieces and tool materials, such as Kıvak [26], Ozcelik and Bayramoglu [27], Turgut et al [24], Karakas et al [28], and Jayakumar et al [29].…”
Section: Cutting Forces and Surface Roughness In Face-milling Of Skd6mentioning
confidence: 99%
“…In milling processes, by using Taguchi method and ANOVA analysis, the cutting forces and surface roughness could be investigated based on a number of factors, such as depth of cut, feed rate, cutting speed, cutting time, workpiece hardness, etc. Several research works had been conducted in different conditions and had also been applied for different workpieces and tool materials, such as Kıvak [26], Ozcelik and Bayramoglu [27], Turgut et al [24], Karakas et al [28], and Jayakumar et al [29].…”
Section: Cutting Forces and Surface Roughness In Face-milling Of Skd6mentioning
confidence: 99%
“…Liu et al 5 studied the surface defect and material removal mechanism and concluded that the most important influence of surface defects is the interaction position relationship of tool and particle. Turgut et al 6 found that the feed per tooth is the most significant factor affecting the surface roughness, followed by the depth of cut, and the spindle speed have the least effect, which was analyzed experimentally by selecting different milling parameters. Wang et al 7 studied the effect of milling parameters on surface roughness and surface morphology during high-speed milling of SiCp/Al composites.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to their unique corrosion resistance, low thermal conductivity and delivering high mechanical properties, stainless steels are used in particularly medical, food, chemical industries, including marine and nuclear power plants and their needs continue to increase every day [1,2]. Custom 450 is a martensitic stainless steel grade, which offers corrosion resistance up to 650°C and its mechanical properties can be increased significantly by heat treatment methods.…”
Section: Introductionmentioning
confidence: 99%